Effect of laminin 332 on motility and invasion in bladder cancer. Issue 8 (14th February 2013) - Kang, Sung‐Gu; Ha, Young‐Ran; Ko, Young‐Hwii; Kang, Seok‐Ho; Joo, Kwan‐Joong; Cho, Hyun‐Yee; Park, Hong‐Seok; Kim, Chul‐Hwan; Kwon, Soon‐Young; Kim, Je‐Jong; Cheon, Jun; Lee, Jeong‐Gu
Abstract: We examined the correlation between laminin 332 and malignancy in bladder cancer patients, and, using a strain of invasive bladder cancer cells, determined whether laminin 332 causes bladder cancer motility and invasion. To investigate the correlation between laminin 332 g2 distribution and patient outcome, we performed a semiquantitative immunohistochemical analysis of 35 paraffin‐embedded samples using the antibody D4B5, which is specific for the laminin 5 γ2 chain. To evaluate the role of laminin 332 in NBT‐II cell motility and invasion, we used a scratch assay and the Boyden chamber chemoinvasion system. Tumor stage and grade were significantly correlated with a loss of laminin 332 γ2 chain from the basement membrane ( p  = 0.001) and its retention in the cytoplasm ( p  = 0.001) (Kruskal–Wallis test). Kaplan–Meier survival curves revealed an association between the risk of progression and cytoplasmic retention of the laminin 332γ 2 chain. In addition, an in vitro scratch assay showed an increase in the migration of cells treated with laminin 332 from their cluster. The Boyden chamber assay showed that laminin 332 potentiated NBT‐II cell invasion. Immunohistochemistry results showed that bladder cancer patients with a higher malignancy expressed more laminin 332. The in vitro scratch and invasion assay showed that laminin 332 stimulated the motility and invasion of bladder cancer cells. The invasion assay explains the correlation between laminin 332 expression and bladder cancer malignancy.